1996
DOI: 10.1017/s0956536100001462
|View full text |Cite
|
Sign up to set email alerts
|

Teotihuacan Valley, Mexico, Postclassic Chronology

Abstract: The Postclassic period in central Mexico was characterized by enormous population growth and expansion of settlement, but the timing of the onset of these processes has been poorly understood. Obsidian tools from residential contexts at the Late Postclassic village of Cihuatecpan in the Teotihuacan Valley have been analyzed to determine the extent of hydration, and thus the amount of time elapsed since the tools were manufactured. Estimated dates of manufacture range betweena.d.1221 and 1568, consistent with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The work of Sanders, Parsons, and colleagues suggested that this commonly held chronological sequence was too simple, and that there was a significant amount of chronological overlap and variation from region to region; more recent excavation projects (Evans and Freter 1996; Parsons et al 1996) have confirmed this spatiotemporal complexity. For example, Parsons, Elizabeth Brumfiel, and Mary Hodge (1996), showed that Teotihuacan residents adopted Coyotlatelco ceramics to their household assemblages significantly later than sites in the southern Basin of Mexico.…”
Section: The Postclassic Basin Of Mexicomentioning
confidence: 99%
“…The work of Sanders, Parsons, and colleagues suggested that this commonly held chronological sequence was too simple, and that there was a significant amount of chronological overlap and variation from region to region; more recent excavation projects (Evans and Freter 1996; Parsons et al 1996) have confirmed this spatiotemporal complexity. For example, Parsons, Elizabeth Brumfiel, and Mary Hodge (1996), showed that Teotihuacan residents adopted Coyotlatelco ceramics to their household assemblages significantly later than sites in the southern Basin of Mexico.…”
Section: The Postclassic Basin Of Mexicomentioning
confidence: 99%
“…This relative chronology was correlated with absolute dates, refined, and expanded to include other central Mexican regions associated with the Aztec Empire as a result of major regional survey and excavation projects beginning in the 1960s (Charlton 1966;Parsons 1966;Blanton and Parsons 1971;Whalen and Parsons 1982;Smith and Doershuk 1991;Evans and Freter 1996;Hare and Smith 1996;Nichols and Charlton 1996;Parsons et al 1996;Hodge 1998;Brumfiel 2005b). Sanders et al (1979) argued that Aztec I and II ceramics were roughly contemporaneous, regional variants used in the Basin of Mexico between AD 1150 and 1350.…”
Section: Postclassic and Colonial Ceramic Chronologies In Central Mexmentioning
confidence: 99%